A Usability Evaluation of Image and Emojis in Graphical Password - Syabila Zabidi, Nur; Mohd Norowi, Noris; Wirza O.K. Rahmat, Rahmita (International Journal of Engineering and Technology, 2018)
This paper presented user preferences in applying image and emojis use in graphical password authentication application.  There is generally lack of two-factor authentication (2FA) approach in mobile devices.  A preliminary study and a user study (N=30) have been conducted to investigate on usability and security issues.  Both of the studies revealed the method of applying picture superiority effect to enhance memorability of graphical password.